Fighting the Cause of Alzheimer’s and GNE Myopathy - Devi, Shreedarshanee; Yadav, Rashmi; Chanana, Pratibha; Arya, Ranjana (Frontiers in Neuroscience, 2018)
Age is the common risk factor for both neurodegenerative and neuromuscular diseases. Alzheimer disease (AD), a neurodegenerative disorder, is the most common cause of dementia in old age people. The major hallmarks of AD are senile plaques composed mainly of extracellular amyloid-β (Aβ) peptides and Neurofibrillary tangles (NFTs) which are formed when hyperphosphorylated tau, a microtubule assembly protein accumulates intracellularly. There are different neuromuscular diseases that share common pathological phenomenon with neurodegenerative disease. GNE myopathy (GNEM) previously correlated to Hereditary Inclusion Body Myopathy (HIBM) or Nonaka Myopathy is an adult onset neuromuscular disorder that is caused by mutation in GNE gene (UDP N-acetylglucosamine 2 epimerase/N-acetyl Mannosamine kinase). Although GNE myopathy is characterized with degeneration of muscle cell, it is shown to have similar disease hallmarks like aggregation of Aβ and accumulation of phosphorylated tau and other misfolded proteins in muscle cell like features found in AD. Similar impairment in cellular functions have been reported in GNE myopathy as compared to AD such as disruption of cytoskeletal network, changes in glycosylation pattern, mitochondrial dysfunction, oxidative stress, upregulation of chaperones, unfolded protein response in ER, autophagic vacuoles, cell death and apoptosis. AD and GNEM are the two diseases with similar phenotypic condition affecting neuron and muscle respectively with no disease treatment. This review represents a comparative outlook of AD and GNEM that could lead to target common mechanism to find a plausible therapeutic for both the diseases.